Guidelines for cell viability assays. Issue 3 (16th September 2020) - Kamiloglu, Senem; Sari, Gulce; Ozdal, Tugba; Capanoglu, Esra
Abstract: Recently, the interest in the application of cell viability assays has been increasing in various fields. Cell viability assays may be broadly classified as (a) dye exclusion assays, (b) colorimetric assays, (c) fluorometric assays, (d) luminometric assays, and (e) flow cytometric assays. Dye exclusion assays include trypan blue, eosin, congo red, and erythrosine B stain assays, whereas 3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5 diphenyl tetrazolium bromide (MTT), 3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium (MTS), 2, 3‐bis‐(2‐methoxy‐4‐nitro‐5‐sulfophenyl)‐2H‐tetrazolium‐5‐carboxanilide (XTT), 2‐(4‐iodophenyl)‐3‐(4‐nitrophenyl)‐5‐(2, 4‐disulfophenyl)‐2H tetrazolium, monosodium salt (WST‐1), 2‐(2‐methoxy‐4‐nitrophenyl)‐3‐(4‐nitrophenyl)‐5‐(2, 4‐disulfophenyl)‐2H‐tetrazolium, monosodium salt (WST‐8), lactate dehydrogenase (LDH), sulforhodamine B (SRB), neutral red uptake (NRU), and crystal violet stain (CVS) assays are among the colorimetric assays. Similarly, resazurin and 5‐carboxyfluorescein diacetate acetoxymethyl ester (5‐CFDA‐AM) assays are based on fluorometric measurements, whereas luminometric assays comprise adenosine triphosphate and real‐time viability assays. Major flow cytometric assays include membrane asymmetry, membrane permeability, and mitochondria assays. In this guideline, the mechanisms and the practice of assessment of the most common cell viability assays applied in research labs are discussed in detail. An ideal cell viability assay should be safe, rapid, reliable, efficient, and time‐ and cost‐effective, and should not interfere with the test compound. Overall, it can be concluded that more than one cell viability assay should be applied in order to obtain reliable results. Abstract : Cell viability assays may be broadly classified as (a) dye exclusion assays, (b) colorimetric assays, (c) fluorometric assays, (d) luminometric assays, and (e) flow cytometric assays. In this guideline, the mechanisms and the practice of assessment of the most common cell viability assays applied in research labs are discussed in detail.